ANALISIS SIKAP DAN KEPUASAN KONSUMEN TERHADAP ATRIBUT PRODUK KARKAS AYAM PEDAGING SEGAR DI PASAR TRADISIONAL KOTA SAMARINDA: ANALYSIS OF ATTITUDE AND CUSTOMER SATISFACTION ON ATTRIBUTES OF FRESH CHICKEN CARCASS IN TRADITIONAL MARKET CITY SAMARINDA - Arif Ismanto; Try Julianda; . Mursidah (Fakultas Peternakan Universitas Papua, 2018)
This research aims to know the attitude of consumers, the level of satisfaction, and what product attributes that are considered consumers before buying the broiler carcass in traditional market of Samarinda City. The data retrieval research conducted during November 2016. The basic method of research is using descriptive method, and itâ€™s implementation with the technique level. The location of the study was chosen intentionally in Samarinda City by taking 3 traditional markets as a sample. The determination of the number of samples is done proportionally and the technique of determining the sampling method by chance (Accidental sampling) with the number of samples of 50 respondents. The type of data used is primary data and secondary data with data collection techniques by observation, interview, and recording. The analysis used is Fishbein Multi Attribute attitude analysis and to analyze satisfaction using Customers Satisfaction Index. The result of the research based on analysis of Fishbein Multiatribut known to consumer attribute value toward color attribute 16.80, weight (16.48), aroma (15.76), skin hygiene (14.57) and price (13.11). Based on Costumer Satification Index the level of customer satisfaction on broiler carcass is 77.11%. Result of research based on analysis of Fishbein Multi Attribute known consumer attitude toward carcass is â€œpositiveâ€ which means consumers are well-receptive to broiler carcass in traditional markets with most attributes considered in the purchase decision of chicken carcasses in traditional markets of Samarinda City is the color of broiler carcasses. The order of attributes from the most considered to the least considered is color, carcass weight, aroma, skin hygiene and broiler carcass price. Based on Customer Satisfaction Index of consumer satisfaction level against broiler carcass is 77.11% who are satisfied category.